Pentingnya Pemahaman Guru BK Konselor dalam Menangani Masalah Siswa Menggunakan Teori Client Centered - Adliya Salsabila; Selfi Purnama Lubis; Yohana Fransisca (JURNAL EDUKASI NONFORMAL, 2023)
A bk teacher has a very important role in the field of guidance and counseling, because basically the bk teacher plays a role in helping to solve problems or difficulties faced by his students. In solving student problems, a bk teacher should have an understanding of the theories that can help solve student problems, one of which is Client Centered theory. This theory sees people as good, optimistic, proactive, constructive, realistic, and trustworthy. A bk teacher should understand this theory so that the bk teacher does not see his students as problematic because basically everyone can find their own life goals.The goal of Person Client Therapy is to create a fully functional individual who can face everyday life without using self-defense techniques. Person Clinet Therapy uses several strategies, including congruence, empathy, and unconditional positive regard. The counselor's ability to empathize with students and provide reflections of their experiences is known as empathy. Without losing their identity, an empathetic counselor will feel what the student is thinking and feeling. However, Person Centered Therapy theory focuses on ways to accept other people's questions and communication and better understand the client or student.The purpose of writing this journal is to find out more deeply that the importance of a bk teacher to be able to understand more about Client Centred theory because if a bk teacher understands this Client Centred theory, he will also be able to understand students better. so that bk teachers can help students to be able to independent themselves in dealing with their problems.The research method used by the author in completing this journal is by collecting research related to library data collection techniques or research whose research objects are examined through various library sources (books, encyclopedias, scientific journals, newspapers, magazines, and documents) forming this kind of research is called library research.The findings obtained by researchers in this journal are like the research of Emma Lusiana, Muswardi Rosra, Ratna Widiastuti which discusses the explanation of the results of research on the use of client centered counseling in improving the positive self-concept of class X students at SMK Kesehatan YPIB in 2016/2017 academic year.So it can be concluded that Client Centered theory has a very important role for a student in order to independent himself and increase positive self-concept in students, so that they can better recognize and understand their own strengths, talents, and abilities. A positive self-concept and self-perception will result in a positive attitude, behavior, and character. This will be beneficial for students and positive things about themselves make them feel confident. With self- confidence, they will not feel depressed and easily get along, socialize, and interact with others.